Advances in physical organic chemistry. - Tidwell, Thomas T., 1939- (Academic Press, 2000)
Advances in Physical Organic Chemistry provides the chemical community with authoritative and critical assessments of the many aspects of physical organic chemistry. The field is a fast developing one, with results and methodologies finding application from biology to solid state physics. The previous volumes in this serial constitute a lasting record of this field and will continue to do so as they are widely used and cited. The serial has maintained high levels of quality and utility over the years. Volume 35, devoted to the study of carbocations and free radicals, includes contributions on excess acidities, the relationship between structure and organic reactivity, electron transfer, bond-breaking and formation, donor/acceptor organizations, and the electron-transfer paradigm for organic reactivity. Readers will also benefit from the comprehensive subject and citation index.